Peran Lembaga Pemberdayaan Masyarakat Desa Mewadahi Partisipasi Masyarakat Dalam Pembangunan Di Desa Balassuka Kecamatan Tombolo Pao Kabupaten Gowa - Fajar, Nur; Tahir, Muhammad; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine the role of the LPMD in accommodating community participation in development and what factors influence the role of the LPMD so that the village development of Balassuka Village, Buttono Pao district, Gowa Regency could be carried out properly. This study used qualitative with a descriptive approach. The Informants in this study were 10 people. Data collection techniques used observation, interviews and documentation. The results of this study indicated that the role of the Village Community Empowerment Institution (LPMD) either as a facilitator was still less than optimal so that in achieving a more prosperous standard of living was very difficult, mediators had  been carried out but not yet maximized so that community interest in participating in any development was still lacking However, motivators and dynamists were still not maximized in order to facilitate community participation in the development of Balasukka Village. The factors that influenced the pran LPMD  were age, education, and employment or income.